PENENTUAN THRESHOLD MENGGUNAKAN ALGORITMA SELF ORGANIZING MAPS (SOM) UNTUK SEGMENTASI REGION KARAKTER PADA PLAT NOMOR KENDARAAN - Apriyanto Alhamad; Vincent Suhartono; Ricardus Anggi Pramunendar (Jurnal Teknologi Informasi - Cyberku (JTIC), 2019)
At this time the era of information technology , the use of automation and intelligent systems are becomingmore and more widespread. Transfortasi Intelligent Systems has received so much attention that manysystems are being developed and applied throughout the world. In a vehicle license plate recognitionsystem consists of several stages , namely pre-processing , license plate detection, the segmentation ofcharacters and the vehicle license plate character recognition . In previous studies determining thethreshold value using Otsu local method by dividing two variants of black and white . In a study usinglocal methods otsu susceptible to interference in the picture . In the study proposes a method of self -organizing map in determining the threshold value . Then from the results of the threshold determinationfollowed by segmenting the characters using the function bouding Box . From the experimental results ofthreshold determination method of self - organizing maps can increase the threshold value of 0.5241 andthe experimental test of character segmentation as measured using the function Means Square Error of6.93E +03 pixels , smaller than the test results of the local segmentation character Otsu method